2014
DOI: 10.1002/2014tc003525
|View full text |Cite
|
Sign up to set email alerts
|

Late Cretaceous-Oligocene magmatic record in southern Mexico: The case for a temporal slab window along the evolving Caribbean-North America-Farallon triple boundary

Abstract: Continental magmatism in southern Mexico is expected to record the eastward displacement of the Farallon-North America-Caribbean triple junction. However, a trench-transversal belt of magmatism in the central western Guerrero State does not fit into a regular pattern of arc migration and reorientation following the formation of the WSW trending Acapulco trench in the Cenozoic. We revised the magmatic pattern of southern Mexico using an updated database and new laser ablation inductively coupled plasma-mass spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 97 publications
(193 reference statements)
0
13
0
1
Order By: Relevance
“…Along the contact between ultramafic and mafic rocks, a lens-like body that containing troctolites and hornblende pegmatites have yielded 40 Ar/ 39 Ar ages of ~38 Ma, consistent with resetting due to the intrusion of the Eocene granites ( Fig. 1; Ferrari et al 2014).…”
Section: Geological Backgroundmentioning
confidence: 78%
“…Along the contact between ultramafic and mafic rocks, a lens-like body that containing troctolites and hornblende pegmatites have yielded 40 Ar/ 39 Ar ages of ~38 Ma, consistent with resetting due to the intrusion of the Eocene granites ( Fig. 1; Ferrari et al 2014).…”
Section: Geological Backgroundmentioning
confidence: 78%
“…Penecontemporaneously, the convergent system of NW of Mexico (Baja California) was undergoing the Alisitos arc assembly and formation of an accretionary complex, as a result of the Farallon plate subduction below NAM (Alsleben et al, ; Boschman et al, ; Schmidt et al, ). On the other hand, the accretionary complex is absent it the southwestern part of Mexico (i.e., SW of the Guerrero Terrane) and was probably truncated by geodynamics of the Farallon‐Cocos‐NAM plates or the Chortís block (Ferrari et al, ; Schaaf et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Age probability diagram for dated volcanic rocks in the Tepic-Zacoalco and Colima grabens. Data from Allan (1986), Moore et al (1994), Nieto-Samaniego et al (1999), Ferrari et al ( , 2013Ferrari et al ( , 2014, Frey et al (2004Frey et al ( , 2007, Centeno-García et al (2011), Valencia et al (2013, Duque-Trujillo et al (2015).…”
Section: Radiometric Datingmentioning
confidence: 99%
“…Ferrari et al (2014) showed that igneous rocks 93-70 Ma in western Mexico are virtually restricted to the Jalisco block; they relate the magmatism to subduction of the Farallon plate to the east beneath Mexico. The Cretaceous igneous suite of the Tecolotlan graben very similar to other Cretaceous to Paleogene magmatic rocks of Jalisco as compiled by Ferrari et al (2014). They are notably different than a Cretaceous to Paleocene suite of adakitic rocks found to the SE.…”
Section: Geochemistry Of the Cretaceous Igneous Rocksmentioning
confidence: 99%
See 1 more Smart Citation